Coastline evolution of the Po River Delta (Italy) by archival multi-temporal digital photogrammetry. Issue 1 (1st January 2019) - Fabris, Massimo
Abstract: Ground deformation areas can be monitored with geomatic methodologies which provide high-precision and high-resolution data. One example is digital aerial photogrammetry, which can be used to reconstruct ground deformations over long periods (80–90 years) with multi-temporal surveys. This technique was used to survey the planimetric deformations of the Po River Delta (PRD), characterized in the past by considerable land subsidence due to intensive pumping of methane water from 1938 to 1961. In the last few decades, land subsidence has been greatly reduced, but is still high compared with natural values, and has influenced the coastline of areas not protected by embankments. In this work, multi-temporal digital photogrammetry was used to study the evolution of the PRD coastline from 1944 to 2014 in the course of seven photogrammetric surveys (1944, 1955, 1962, 1977, 1999, 2008 and 2014). Results of the multi-temporal analysis were correlated with available subsidence rates (from levelling, for the past, and from synthetic aperture radar, for the period 1992–2017): this study show agreement between land subsidence and areas submerged by the sea, although they are also greatly influenced by human activities and sea level rise which increasingly exposing the area to the risk of widespread flooding.